Prevalencia de lesiones músculo esqueléticas en odontólogos que ejercen en la ciudad de Loja - Medina Salazar, Katherine Cecibel (2019)
Musculoskeletal disorders related to repetitive work practices are a major problem in modern societies and refer to all types of tissue damage in the musculoskeletal system and nerves; Dentists are more likely to have musculoskeletal disorders due to their work. Such discomfort is more frequent in the neck, shoulders and back, but it also affects other body parts. (Taib MFM, 2017). In our study, 96 dental professionals who work in the city of Loja were selected; they were surveyed in order to establish the prevalence of musculoskeletal injuries as a result of working in dental clinics, and assess the scale of pain; besides, to define which are the most affected areas the visual analog scale (VAS) was used. A 61% prevalence of discomfort in the musculoskeletal system was identified in the study population. In addition, the injuries that were mostly diagnosed are: muscle fatigue in men with 22% and 27% in women and muscle contracture in women with 15% and 20% in men. Moreover, 35% of the sample population reported that the most affected part was the cervical area, and the discomfort caused was perceived as tolerable 17%. Keywords: skeletal muscle disorder, work practices, occupational health